Light absorption properties of brown carbon in the high Himalayas. Issue 16 (23rd August 2016) - Kirillova, Elena N.; Marinoni, Angela; Bonasoni, Paolo; Vuillermoz, Elisa; Facchini, Maria Cristina; Fuzzi, Sandro; Decesari, Stefano
Abstract: The light‐absorbing properties of water‐soluble brown carbon (WS‐BrC) and methanol‐soluble brown carbon (MeS‐BrC) were studied in PM10 aerosols collected at the "Nepal Climate Observatory‐Pyramid" (NCO‐P) station (5079 m above sea level) during the period 2013–2014. The light absorption coefficients of WS‐BrC and MeS‐BrC were the highest during the premonsoon season and the lowest during monsoon. MeS‐BrC absorbs about 2 times higher at 365 nm and about 3 times more at 550 nm compared to WS‐BrC. The mass absorption cross section (MAC) of WS‐BrC measured at 365 nm is similar to that observed previously at South Asian low‐altitude sites. Fractional solar radiation absorption by BrC compared to BC considering the full solar spectrum showed that WS‐BrC absorbs 4 ± 1% and MeS‐BrC absorbs 9 ± 2% compared to BC at NCO‐P. Such ratios become 8 ± 1% (for WS‐BrC respect to BC) and 17 ± 5% (for MeS‐BrC respect to BC) when accounting for correction factors proposed by previous studies to convert absorption coefficients in bulk solutions into light absorption by accumulation mode aerosol particles. These results confirm the importance of BrC in contributing to light‐absorbing aerosols in this region of the world. However, the BrC absorption at 550 nm appears small compared to that of BC (1–5%, or 3–9% with conversion factors), and it is lower compared to global model estimates constrained by Aerosol Robotic Network observations. Finally, our study provides no clear evidence of a change in the fractional contribution of BrC with respect to BC to light absorption in the middle troposphere respect to the Indo‐Gangetic plain boundary layer. Key Points: Light absorption coefficient of BrC in the high Himalayas has a strong seasonal variability BrC absorbs on average 4 +/‐ 1% (WS‐BrC) and 9 +/‐ 2% (MeS‐BrC) of solar radiation compared to BC BrC light absorption properties in the high Himalayas are similar to those at low altitudes